Application of Basel Committee's New Standards of Internal Audit Function: A Road Map towards Banks' Performance - Al-Matari, Yahya Ali; Hassan, Sallahuddin; Alaaraj, Hassan (International Journal of Economics and Financial Issues, 2016)
The high level of completion along with deceitful financial reporting has recently pointed the increasing consideration of researchers and academicians on the internal controls and internal audit functions (IAF). IAF in banks has several principles that are essential to be adhered. The bank's management bears the final responsibility to apply these principles properly and effectively to avoid such corporate scandals that would shake the confidence of investors and make it hard for organizations to enhance equity within the stock market. Thereby, they would need to understand the internal factors which influence their profitability performance. The main purpose of this paper is to develop the relationship between new standards of IAF issued by Basel Committee (2012) and banks' performance. In addition, it presents a theoretical research framework to understand this relationship supported by literature review from recent studies. The literature review indicates that practicing IAF creates discipline and enhances effectiveness of control and governance practices which are necessary to promote performance in the banks. Due to limitations of literature in bank sector, future studies are suggested to broaden the research empirically and highlight more on the effective IAF that can lead to better banks' performance. Keywords: Internal Audit Function, Basel Committee, Corporate Governance, Agency theory, Institutional Theory, Bank Performance. JEL Classification: G2, M42